Personal Responsibility Correlation in View of Self-Regulated Learning and Learning Autonomy University Students - Handaka, Irvan Budhi; Taufiq, Agus; Yusuf, Syamsu; Herdiansyah, Diki; Tiskova, Navy Glenda (Universitas Ahmad Dahlan, 2024)
As explained, personal responsibility is an individual's skills in taking responsibility for all decisions and actions and the results and impacts on others. A sense of responsibility can affect student academic achievement, so having a sense of personal responsibility, especially in the learning process, becomes important. Personal or personal responsibility can be developed through self-regulated learning and learning autonomy. So, this study aims to determine whether there is a correlation between personal responsibility with self-regulated learning and learning autonomy. The method used in this study is quantitative with a correlational type of research involving 141 students from semester 2 to semester ten aged 18 to 24 years. The data collection technique uses three instruments (personal responsibility, self-regulated learning, and autonomy learning). This study's results indicate a correlation between the three variables, namely personal responsibility, self-regulated learning, and autonomy learning (p> 0.000). The existence of this relationship shows that it is important for students to cultivate personal responsibility so that they can manage the learning process without depending on others (independently).